A generalized isogeometric boundary element method for the uncertain analysis of infinite domain two-dimensional acoustic problems - Yang, Yan; Huo, Ruijin; Yuan, Xiaohui; Wu, Wenbo (Frontiers in Physics, 2023)
The key aim of the paper is to provide a new n-th generalized order perturbed isogeometric fast multistage technique of boundary elements to compute the propagation of time harmonics in an infinite region. Structural geometry and boundary integral equations are constructed by using nonuniform rational B-splines. The source of system uncertainty is believed to be the incident plane wave number's unpredictability. The actual field depending on input random variables is simulated using the extended n-th order perturbation approach. The field values and kernel values for boundary integral formulas are generated via the n-th order generalized series of Taylor expansions using perturbation parameters. The singular integral is solved using singularity subtraction, and the fast multipole approach is utilized to speed up the process. The effectiveness and correctness of the proposed algorithm are verified by Monte Carlo simulation with numerical examples.